Death blossoms: reflections from a prisoner of conscience - Abu-Jamal, Mumia (Plough Pub. House, 1997)
"Profound meditations on life, death, freedom, family, and faith, written by radical Black journalist, Mumia Abu-Jamal, while he was awaiting his execution"--